Exporters in the Time of COVID-19 Pandemic: Evidence from Indonesia - Realita Eschachasthi (Institute for Economic and Social Research, 2022)
The export of Indonesia has contracted rapidly in response to the COVID-19 outbreak. However, little is known about the crisis-trade relationship, which is important for the policymakers to design the relevant policies. To that end, this study examines how exporters adjust in the time of pandemic as well as estimates the impact of COVID-19 on export performance by using microdata of monthly export transactions from January 2019 to August 2020. This relationship is analyzed by employing intensive and extensive margins as well as a panel fixed effects specification. The result shows that capital goods, mainly manufactured products, have been hit the hardest compared to consumption and intermediate goods. The evidence also suggests that the exporters have been primarily affected at the extensive margin or leaving the market. During the crisis, the rate of ceasing export transactions is approximately 40%, while the rate of decline in export value is 14%. The aftermath of COVID-19 is expected to disrupt export performance by 0.15 percentage points of mid-point growth. The result is robust subsequent to performing several alternative specifications. Finally, the study discovers that the virus does not discriminate; it hits all exporters regardless of their size.